Triggers of breathlessness in inducible laryngeal obstruction and asthma. Issue 11 (6th September 2020) - Haines, Jemma; Chua, Sarah H. K.; Smith, Jacky; Slinger, Claire; Simpson, Andrew J.; Fowler, Stephen J.
Abstract: Background: Inducible laryngeal obstruction (ILO) is often misdiagnosed as, or may coexist with, asthma. Identifying differences in triggering factors may assist clinicians to differentiate between the two conditions and could give mechanistic insights. Objective: To identify and compare patient‐reported triggers in ILO and asthma. Methods: This was a two‐part study. Initially, we conducted a retrospective case note review of the triggers of ILO from endoscopically confirmed ILO patients to generate a Breathlessness Triggers Survey (BrTS). Triggers were categorized as scents, environmental factors, temperature, emotions, mechanical factors and daily activities. Secondly, ILO and/or asthma patients completed the BrTS prospectively, rating the likelihood of each item triggering their symptoms using a five‐point Likert scale (strongly disagree to strongly agree). Chi‐square testing was performed to compare responses by cohort. Results: Data from 202 patients with ILO [73% female, mean (SD) age 53(16) years] were included in the case note review. For the prospective study, 38 patients with ILO only [63% females, age 57(16) years], 39 patients with asthma only [(56% female, age 53(13) years] and 12 patients with both ILO and asthma [83% female, mean age, 57 (14) years)] completed the BrTS. The triggers identified in the case note review were confirmed in the independent sample of patients with ILO and/or asthma and identified several difference in prevalence of the triggers between disease types. Mechanical factors (talking [ P  < .001], shouting [ P  = .007] and swallowing [ P  = .002]) were more common in the ILO cohort compared to patients with asthma. Environmental factors (pollen/flowers [ P  = .005] and damp air [ P  = .012]) were more common in asthma. There were no differences between groups in frequency of reporting scents as triggers (except for vinegar, more common in ILO, P  = .019), temperature, emotions or daily activities. Conclusion: There were notable differences between patient‐reported triggers of ILO and asthma, which may support clinician differential diagnosis.